Trends Analysis of Dengue Hemorrhagic Fever in Campurejo East Java, Indonesia 2019-2021 - Dita Meylinda Hafsari (Ficco Scientific Corner, 2024)
Background: Dengue fever is a disease with a fairly high prevalence in Indonesia. Currently, dengue fever is a public health problem in Indonesia, with a tendency to increase in number of cases and spread. The aim of this study is to determine the pattern of dengue fever based trends at the Campurejo Health Center, Kediri City in 2019 to 2021. Methods: This is an observational descriptive study. The data collection is to collect the required data or information, including the data on dengue fever cases based on age, gender and place of residence, larva-free number data for each sub-district of the Campurejo Health Centre. Results: In 2019 The area with the highest number of cases is Bandar Kidul village (15 cases). In 2020, the areas with the most cases were Bandar Kidul village (16 cases) and Lirboyo village (13 cases). In 2021, The area with the highest number of cases is Bandar Kidul Village (9 cases). Conclusion: The number of dengue hemorrhagic fever cases will decrease between 2019 and 2021, and the areas with the highest number of cases will also change.